Early-stage anomalies in the sea urchin (Paracentrotus lividus) as bioindicators of multiple stressors in the marine environment: Overview and future perspectives. (15th October 2021) - Gambardella, Chiara; Marcellini, Francesca; Falugi, Carla; Varrella, Stefano; Corinaldesi, Cinzia
Abstract: The morphological anomalies of the early development stages of the sea urchin Paracentrotus lividus, caused by exposure to environmental stressors, are used as biomarker in ecotoxicological and ecological investigations. Here, we reviewed the available literature and classified the embryo and larval anomalies identified so far, to highlight potential commonalities or differences related to the biological action of the different stressors and their ecological impact. Morphological anomalies are influenced by a) the developmental stage of exposure to stressors; b) the intensity of the stress; c) the intra- and inter-cellular mechanisms affected by the exposure to environmental agents. The classification and analysis of embryo and larvae anomalies, either observed by the authors of this review and reported in literature, indicate that sea urchin abnormalities, caused by exposure to different stressors, can be very similar among them and classified into 18 main types, which can occur individually or mixed. All anomalies can be used to calculate an Index of Contaminant Impact to assess the impact of multiple stressors and to identify relationships between morphological anomalies and compromised biological mechanisms. This approach could be useful for a first screening of the presence of potential stressors impairing the growth and development of the early life stages of marine organisms, thus providing a relevant advancement for in future monitoring activities devoted to assess the health status in coastal marine ecosystems. Graphical abstract: Image 1 Highlights: Sea urchin anomalies, caused by multiple stressors, can be grouped into 18 types. Anomaly severity and evolution depend on stressor concentration/intensity. Stressors cause similar anomalies impinging on the same cellular mechanisms. Embryo and larval anomalies can be used to predict the environmental impact degree.